2010
DOI: 10.1038/nchembio.481
|View full text |Cite
|
Sign up to set email alerts
|

Specific Btk inhibition suppresses B cell– and myeloid cell–mediated arthritis

Abstract: Bruton's tyrosine kinase (Btk) is a therapeutic target for rheumatoid arthritis, but the cellular and molecular mechanisms by which Btk mediates inflammation are poorly understood. Here we describe the discovery of CGI1746, a small-molecule Btk inhibitor chemotype with a new binding mode that stabilizes an inactive nonphosphorylated enzyme conformation. CGI1746 has exquisite selectivity for Btk and inhibits both auto- and transphosphorylation steps necessary for enzyme activation. Using CGI1746, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
298
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(313 citation statements)
references
References 46 publications
12
298
2
1
Order By: Relevance
“…The results demonstrated that ibrutinib did not adversely affect the phagocytic ability of monocytes despite its ability to block Fc␥R-mediated TNF␣ production by monocytes. We also tested the effects of the more selective Btk inhibitor CGI-1746 (28) and found that it was equal in its ability to block Fc␥R-mediated cytokine production in monocytes (data not shown). This is in contrast to the findings with NK cells, where ibrutinib, but not CGI-1746, blocked NK-cell antibody-dependent cellular cytotoxicity because activated NK cells express Itk, which is not inhibited by CGI-1746 (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that ibrutinib did not adversely affect the phagocytic ability of monocytes despite its ability to block Fc␥R-mediated TNF␣ production by monocytes. We also tested the effects of the more selective Btk inhibitor CGI-1746 (28) and found that it was equal in its ability to block Fc␥R-mediated cytokine production in monocytes (data not shown). This is in contrast to the findings with NK cells, where ibrutinib, but not CGI-1746, blocked NK-cell antibody-dependent cellular cytotoxicity because activated NK cells express Itk, which is not inhibited by CGI-1746 (18).…”
Section: Discussionmentioning
confidence: 99%
“…Btk inhibition results in reduced Fc␥R-mediated cytokine production in monocytes and macrophages (19,27,28). However, the effect of reduced Btk function on phagocytosis is less clear, with studies showing significant (29 -31) or only marginal (32) effects.…”
Section: Ibrutinib Suppresses Fc␥r-mediated Cytokine Production But Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic absence of Btk in humans is associated with impaired B cell development and agammaglobulinemia. Small molecule inhibitors of Btk are available and currently used for the treatment of mantle cell lymphoma, while others are in early development for RA [58]. The variable responses thus far detected to kinase inhibitors however reflects our relatively limited understanding of the true cellular hierarchy of these pathways at the synovial pathogenetic level.…”
Section: B Cells In Pathogenesis Ofmentioning
confidence: 99%
“…These include Tocilizumab (anti-IL-6R) (Fleischmann et al, 2006;Jones et al, 2010) and Anakinra, a recombinant IL-1 receptor antagonist, as well as Bevacizumab, an antibody that targets vascular endothelial growth factor (VEGF) and hence may reduce neovascularisation that pannus formation depends upon. A variety of small molecule inhibitors designed to target critical elements of the B cell receptor, T cell receptor or cytokine signalling pathways such as inhibitors of IKK2, PDE4 and Btk (Bruton's tyrosine kinase), have shown interesting results in some animal models of arthritis, as have clinical trials with the syk inhibitor R788 (Podolin et al, 2005;Lindstrom et al, 2010;Di Paolo et al, 2011). The p38 inhibitors however, which showed such promise in animal models have not lived up to expectations in clinical trials and have not progressed beyond phase II (Genovese, 2009).…”
Section: The Cellular Basis Of Ra and Current Therapiesmentioning
confidence: 99%